Implementation of Boarding School Learning in Building Religious Character at SMA Daarul Qur'an Bandung - Fitri Handayani; Muhammad Hasan Basari; Nurhidayah Nurhidayah; Devi Fatwanti; Otisia Arinindyah (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2025)
The low understanding of religious values among students remains a problem that needs to be addressed. The purpose of this research is to analyze and develop a boarding school learning implementation model to build religious character in high school. This study uses a qualitative approach with a descriptive method, and data collection techniques is done through interviews, observations, and documents. The results are that the implementation of boarding school learning is carried out through Quran memorization (tahfidz), memorizing the Quran at least up to the 30th juz, or memorizing all 30 juz, as well as integrating the Quran and Islamic studies into the learning. The Quran memorization program, or Islamic studies, consists of seven lessons: fiqh, tawhid, hadith, tafsir, Arabic language, history, and tajwid. Additionally, the Tahfizh Qur'an program, which means memorizing the Quran, is held daily after Subuh, Asar, and Isha prayers, with one verse each day. The habit of praying obligatory prayers in congregation on time and performing daily routine worship, as well as good manners, ethics, and noble character. The conclusion is that the implementation of boarding school-based learning in building religious character at SMA Daarul Quran Bandung, is carried out through the integration of the Al-Quran and Islamic studies in intra-curricular learning activities, extra-curricular activities and Islamic boarding school activities with Islamic studies and Quran memorization for twenty-four (24) hours in a comprehensive and integrated manner.